Citra Diri terhadap Kecenderungan Hedonistic Lifestyle pada Mahasiswa - Lucky Fatmala Dewi; Siti Nur’aini; Nuraini Kusumaningtyas (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2021)
Hedonistic lifestyle is a lifestyle that is intended for pleasure seeking, one of the factors that influence is self image. The tendency of hedonistic lifestyle in students is intended to show identity, personal personality, and the formation of characteristics so as to create good interpersonal relationships and facilitate social interaction. The purpose of this study was to determine the effect of self-image on the tendency of hedonistic lifestyle, the level of hedonistic lifestyle, and the image of self-image in students. This study uses a quantitative method of causal relationships with the sampling technique used is cluster sampling of 348 students. The scale used is a Likert scale with the results of the validity and reliability test is overall valid and reliable. The results of the analysis state that there is an influence between the two variables with a significance coefficient of 0.573> 0.05. The analysis test results showed that there was a significant positive relationship between self-image and hedonistic lifestyle. Descriptive hedonistic lifestyle test results showed high categories (50.9%), low (49.1%), self-image showed high categories (50.6%), low (49.4%). Descriptive test results showed no differences in terms of gender, age but there were differences in terms of allowance.